An Error Study of Google Translate from Indonesian into German - Mannahali, Misnah (Universitas Negeri Makassar, 2024)
Abstract. This research aims to find out linguistic errors contained in the translation results from Indonesian into German produced by students using Google Translate. This research uses a qualitative descriptive method, defining, interpreting and correcting linguistic errors that appear in the results of Indonesian translations into German with the help of Google Translate. The data collection technique was through giving a translation test to 16 fifth semester students. This research found that several errors, such as errors in choosing words that were not appropriate to the context, using inappropriate sentence structure or rules, were caused by differences in language rules between Indonesian and German. Google Translate in this case is indeed very helpful for translators in translating during the translation process, but translators must be aware that the translations produced by Google Translate still require improvements, especially in terms of choosing the right words according to the context and arranging sentences correctly. Keywords: Translation, Translate, Google Translate, Indonesian, German